Is there any effect (s) of fenugreek seeds aqueous extract on the regularity of estrous cycle and quantity of ovarian follicles of female rats…? - Allow, Ahmed Kaid Naji; Mohamed Bakrim, Norbaiyah; Zainab, Yousof; Al-Ani, Imad Matloub Dally; Mohd Hassan, Norazian; Al-Kubaisi, Muna Khaleel Dheyab; Mustafa, Imad Al-Deen (2015)
INTRODUCTION Fenugreek (Trigonella foenum-gracum) is an annual plant that is cultivated in the Mediterranean region, North Africa, Yemen and India.[1, 2] Currently, several medicinal plants species are widely used as antifertility agents by the local population in different parts of the world; these plants possess different types of antifertility activities such as anti-implantation, abortification, ecobolic, estrogenic and spermicidal.[7] Fenugreek showed a decrease in testosterone levels and a decrease in number of seminiferous tubules and abnormal spermatogenesis in rabbits.[8] Treatment of female rats with fenugreek lead to a significant decrease in follicular-stimulating (FSH) and luteinizing hormones (LH) and estradiol levels.[9]. The present study was designed to evaluate the potential effects of fenugreek aqueous extract by examining the regularity appearance estrous cycle stages, relative ovarian weights, and the number of secondary and antral follicles as well as corpora lutea in female Sprague Dawley rats.